Antidiabetic action of prebiotic convenient food mixes: An in vivo rat study - Subbulakshmi, B; Gurumeenakshi, G; Praveena, S; Muralidharan, B (Plant Science Today, 2025)
Diabetes is a chronic multi-system disease having long term health consequences. This study investigated the role of multi millet enriched prebiotic convenient food mixes in alleviating the diabetic complications in induced diabetic rats. The multi millets and leafy vegetables viz., drumstick leaves (Moringa oleifera) and spinach leaves (Spinacia oleracea) were used to formulate convenient food mixes namely chappathi and dosa mix as well as evaluated the antidiabetic effect of these mixes in alloxan induced diabetic albino rats. All the developed four mixes are scored higher acceptability and provided with high amounts of fibre, iron and beta carotene. The study comprises 6 groups of 6 animals each. Group 1 served as non-diabetic control, Group 2 as diabetic control and groups 3, 4, 5 and 6 served as treatment groups. Diabetic was induced in rats by administration of alloxan monohydrate (150 mg/kg) through the intra peritoneal route. Treatment groups (G3 - G6) received diet of (100 mg/kg of body weight) multi millets drumstick leaves chappathi mix (T1); multi millet spinach leaves chappathi mix (T2); multi millet drumstick dosa mix (T3) and multi millet spinach leaves dosa mix (T4) respectively. After the 28 days of treatment, diabetic rats showed a highly significant (p>0.0001) reduction in blood glucose levels when compared to diabetic control and non-diabetic groups. The study showed the multi millets and leafy vegetable based instant mixes have an effective antidiabetic property which controls the blood glucose levels in the rats and this study will create a new avenue to formulate the special convenient food mixes for diabetic people.